(untitled) (Early Childhood Education & Parenting (ECEPA), 2025)
The aim of educational characters is to build a strong nation where people become more tolerant, solidarity, and noble morals. Therefore, character education in early childhood is considered important because at an early age children’s character is easy to shape because children imitate and absorb behavior from the surrounding environment more quickly. The effort in passing on culture to early childhood in Tana Toraja Regency involves early childhood in cultural activities. One of the activities involving early childhood is the Rambu Solo’ traditional ceremony. The purpose of this study was to determine the character education values reflected in the Rambu Solo’ traditional ceremony for early childhood. This study is qualitative with semi ethnographic approach. The data collection techniques are observation, interview, and documentation. The results of this study are the value of character education that exists in the Rambu Solo’ ceremony for early childhood is religious, social care, tolerance, discipline, and curiosity. Furthermore, one of the form of early childhood involvement in the Rambu Solo’ ceremony is receiving guests that adjusted to the physical abilities of the children.